Development of a Progressive Hermeneutics Model in Sharia Economic Dispute Resolution: A Case Study of the Majene Religious Court Decision Number 1/Pdt.G.S/2024/PA. Mj - Nuzha, Nuzha; Ardiansyah; Usman, Ilham (Faculty of Law, Universitas Pekalongan, 2025)
This article presents a progressive hermeneutic model as an interpretive framework for resolving Sharia economic disputes, using a case study of the Majene Religious Court Decision Number 1/Pdt.G.S/2024/PA.Mj. This research is driven by the finding that the judge’s hermeneutic approach in Sharia economic cases remains dominated by a legal-formal orientation, particularly in cases resolved through a peace deed. The standard clauses of Islamic banking, the limited scope for judicial interpretation, and the weak protection of vulnerable parties within the contractual structure indicate the need for a more responsive hermeneutic framework, grounded in the principle of substantive justice and based on maqāṣid al-shari’ah. Using normative-empirical methods, this study develops a progressive hermeneutic model grounded in three pillars: normative texts, socio-economic contexts, and the moral goals of Islamic law.